2013
DOI: 10.1093/aje/kws330
|View full text |Cite
|
Sign up to set email alerts
|

Association of Functional Polymorphism rs2231142 (Q141K) in the ABCG2 Gene With Serum Uric Acid and Gout in 4 US Populations

Abstract: A loss-of-function mutation (Q141K, rs2231142) in the ATP-binding cassette, subfamily G, member 2 gene (ABCG2) has been shown to be associated with serum uric acid levels and gout in Asians, Europeans, and European and African Americans; however, less is known about these associations in other populations. Rs2231142 was genotyped in 22,734 European Americans, 9,720 African Americans, 3,849 Mexican Americans, and 3,550 American Indians in the Population Architecture using Genomics and Epidemiology (PAGE) Study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
68
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 47 publications
7
68
1
1
Order By: Relevance
“…Nonetheless, direction of genetic effect (odds ratio) observed among AfricanAmericans was consistent with the result in EuropeanAmericans as well as with previous reports in the literature (Table 2) [47]. Direction of effect and coded allele frequency (CAF) were also consistent with previous reports in African-Americans [48].…”
Section: Replicating Associationssupporting
confidence: 91%
See 1 more Smart Citation
“…Nonetheless, direction of genetic effect (odds ratio) observed among AfricanAmericans was consistent with the result in EuropeanAmericans as well as with previous reports in the literature (Table 2) [47]. Direction of effect and coded allele frequency (CAF) were also consistent with previous reports in African-Americans [48].…”
Section: Replicating Associationssupporting
confidence: 91%
“…Also known as Q141K, rs2231142 is a missense variant associated with gout as identified by a GWAS performed in the Framingham and Rotterdam cohorts [47], and subsequently replicated in multiple populations [48]. The minor allele (A) frequency was 0.17 in cases (n = 363) and 0.11 in controls (n = 5528).…”
Section: Replicating Associationsmentioning
confidence: 99%
“…Dehghan et al (2008) conducted a genome-wide study in a Framingham cohort and a Rotterdam cohort, and reported that an SNP in the ABCG2 gene, rs2231142, displayed strong evidence of an association with uric acid levels (P < 10 -60 ). A meta-analysis of 39,853 people from four different populationbased samples (European Americans, African Americans, Mexican Americans, and American Indians) demonstrated that the functional variant rs2231142 (Q141K) in the ABCG2 gene was significantly associated with both SUA level and gout (Zhang et al, 2013). The SLC2A9 gene, which has the chromosomal locus 4p16.1, encodes a protein called solute carrier family 2, facilitated glucose transporter member 9 (SLC2A9), also known as glucose transporter type 9 (GLUT9); it is a glucose transporter and plays a significant role in maintaining glucose homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, allelic variants in 3 urate transportersdURAT1, ABCG2, and SLC2A9dhave been linked with hyperuricemia in American Indians in the Strong Family Heart Study, and the allelic variant in SLC2A9 has also been shown to strongly predict the presence of CKD by a reduction in estimated glomerular filtration rate. 68,69,84 The allelic variant in URAT1 has also been linked with metabolic syndrome and obesity in white populations. 137 We have also identified via Yale's ALFRED and Broad Institute's ExAC databases (http:// alfred.med.yale.edu/, http://exac.broadinstitute.…”
Section: Sugar and Uric Acid And Their Potential Role In Increasing Tmentioning
confidence: 99%